Gambaran Pengetahuan Orang Tua tentang Kejadian Speech Delay pada Balita di Wilayah Kerja Puskesmas Samata Kabupaten Gowa - Ilmatiana Ilmatiana; Fanny Dewi Sartika; Nurhijrani Nurhijrani; Sennahati Sennahati (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2026)
Speech delay is a common developmental disorder in children. This condition is characterized by language skills that lag behind those of children of the same age. Language skills are an important aspect that children need to master, but not all children are able to master this skill. Speech delays can be identified by inaccurate word usage, which is characterized by unclear pronunciation and communication using only sign language, making it difficult for parents and others around the child to understand, even though the child can actually understand what is being said. Therefore, early detection of speech and language disorders in children is crucial for the child's care, starting with parents, family, and doctors. Objective: To determine parental knowledge about speech delay in toddlers in the Samata Community Health Center, Gowa Regency. Research Method: A descriptive observational study using a survey method was used. The author only sought to determine parental knowledge about speech delay in toddlers in the Samata Community Health Center, Gowa Regency. Research Results: A survey of 30 respondents was obtained, indicating that most respondents (53.3%) had good knowledge about speech delay in toddlers, followed by 43.3% with adequate knowledge, and 3.3% with inadequate knowledge. Conclusion: On average, respondents had good and adequate knowledge about speech delay. Recommendation: An early detection program for toddlers in the Samata Community Health Center, Gowa Regency, is recommended.